Not all who wander are lost: prospecting and settlement of male floaters in the spotless starling - Redondo, Iraida; Fusté, Roger; Muriel, Jaime; Gómez-Llanos, Eduardo; Monclús, Raquel; Pérez-Rodríguez, Lorenzo; Gil, Diego (OXFORD UNIV PRESS INC, 2025)
Floaters are non-breeding individuals that lack a territory or a breeding site. In many species, they can be seen visiting the territories of conspecifics before obtaining their own breeding site. Prospecting behavior is hypothesized to benefit floaters through information acquisition, enhanced site familiarity and dominance over other floaters. Here, we used detections of PIT-tagged male floaters in a population of spotless starlings (Sturnus unicolor). We investigated how floater activity varied across breeding stages and how their visits influenced subsequent nest site selection. We also tested whether distance, reproductive success, and phenotype and fate of the former owner influenced final settlement. We found that floater activity increased during the nestling-rearing period as nestling age increased. Floaters were more likely to breed near the area where they had been detected the previous year, suggesting that prospecting allows males to secure a foothold in their future settlement area. Although prospecting was higher in nests with a higher number of nestlings, neither breeding success, phenotype, nor provisioning rate of the last owner were related to nest choice, suggesting that public information is not used by males to decide where to settle. However, we found that floaters were more likely to breed in nest boxes where the previous owner had disappeared from the colony, suggesting that visits by male floaters in this species allow them to detect new vacancies. Our results suggest that prospecting might serve several non-mutually exclusive functions. Further studies in non-saturated colonies could shed light on the functional aspects of prospecting.